Efektivitas Crossword Puzzle dalam Pembelajaran Bahasa Arab Sebagai Inovasi Pembelajaran Daring di Masa Pandemi Covid-19 - Afif Kholisun Nashoih; Miftachul Janah (Al-Lahjah, 2022)
The purpose of this study was to improve reading skills by using crossword puzzle in class X MIPA MAN 3 Jombang. This study used a quasi-experimental method with a non-equivalent control group pre-test post-test design. The population in this study was class X MIPA MAN 3 Jombang while the sample was X MIPA 7 as the control class and X MIPA 3 as the experimental class. Data were analyzed descriptively and inferentially. From the test data, it can be seen that the average value of the experimental class and the control class with the number of students 40 each class has increased. The average pre-test value of the control class is 56.75 and the average post-test value is 79.25 while the average pre-test value of the experimental class is 57.5 and the average post-test value is 87,5. Based on the results of the SPSS analysis 16.0, obtained sig. (2-tailed) of the experimental class and the control, class post-test is 0.00, which means lower than 0.05. So it can be concluded that H1 is accepted then there is a significant difference between the experimental class post-test and the control class post-test.